Non-invasive ventilation and continuous positive pressure ventilation in emergency departments: where are we now?. Issue 4 (20th March 2008) - Bolton, R; Bleetman, A
Abstract : A number of emergency departments have introduced non-invasive positive pressure ventilation (NIV) and continuous positive airway pressure (CPAP) for patients presenting with acute respiratory failure. It is thought that early non-invasive respiratory support will avoid the need for invasive ventilation in many cases. This literature review studied current knowledge of NIV and CPAP in the acute setting with the aim of creating simple guidelines for hospitals initiating early non-invasive ventilatory support in emergency departments. NIV is effective in reducing intubation and mortality rates in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) and CPAP is effective in reducing mortality in patients with cardiogenic pulmonary oedema, especially when implemented early. NIV and CPAP were also found to be effective in some other causes of acute respiratory failure. There is a role for non-invasive respiratory support in emergency departments.